Nolo's encyclopedia of everyday law : answers to your most frequently asked legal questions (Nolo, 2023)
Offers an overview of law, as it applies to everyday life, including information on credit and debt, workplace rights, wills, divorce, social security, landlord-tenant laws, child custody and visitation, and criminal law.